Tính tổng 1.2 + 2.3 +3.4+.......... + 49.50
Tính tổng (1.2)+(2.3)+(3.4)+...+(49.50)=?
A=1.2+2.3+3.4+...+49.50
Tính tổng A ?
3A = 1.2.3 + 2.3.3 + 3.4.3 + ... + 49.50.3
3A = 1.2.3 - 0.1.2 + 2.3.4 - 1.2.3 + 3.4.5 - 2.3.4 + ... + 49.50.51 - 48.49.50
3A = 49.50.51
A = 41650
\(A=1.2+2.3+3.4+....+49.50\)
\(3A=1.2.3+2.3.3+3.4.3+....+49.50.3\)
\(3A=1.2.3+2.3.\left(4-1\right)+3.4.\left(5-2\right)+....+49.50.\left(51-48\right)\)
\(3A=1.2.3+2.3.4+3.4.5+....+49.50.51\)
\(3A=49.50.51=124950\)
\(\Rightarrow A=\frac{124950}{3}=41650\)
Tính tổng
1.2+2.3+3.4+...+49.50
Đặt A = 1.2 + 2.3 + 3.4 + ... + 49.50
=> 3A = 1.2.3 + 2.3.3 + 3.4.3 + ... + 49.50.3
= 1.2.3 + 2.3(4 - 1) + 3.4.(5 - 2) + .... + 49.50.(51 - 48)
= 1.2.3 + 2.3.4 - 1.2.3 + 3.4.5 - 2.3.4 + ... + 49.50.51 - 48.49.50
= 49.50.51
Khi đó A = 49.50.51 : 3 = 41650
cho A = 1/1.2+1/2.3+1/3.4+...+1/49.50 ; cho B = 1.2+1.3+3.4+....+49.50
tính 50mủ 2A - B/17
\(A=\frac{1}{1.2}+\frac{1}{2.3}+\frac{1}{3.4}+...+\frac{1}{49.50}\)
\(=\frac{2-1}{1.2}+\frac{3-2}{2.3}+\frac{4-3}{3.4}+...+\frac{50-49}{49.50}\)
\(=1-\frac{1}{2}+\frac{1}{2}-\frac{1}{3}+\frac{1}{3}-\frac{1}{4}+...+\frac{1}{49}-\frac{1}{50}\)
\(=1-\frac{1}{50}=\frac{49}{50}\)
\(B=1.2+2.3+3.4+...+49.50\)
\(3B=1.2.3+2.3.3+3.4.3+...+49.50.3\)
\(=1.2.3+2.3.\left(4-1\right)+3.4.\left(5-2\right)+...+49.50.\left(51-48\right)\)
\(=1.2.3+2.3.4-1.2.3+3.4.5-2.3.4+...+49.50.51-48.49.50\)
\(=49.50.51\)
\(B=\frac{49.50.51}{3}=49.50.17\)
\(50^2.A-\frac{B}{17}=49.50-49.50=0\)
Tính
a) S= 1.2+2.3+3.4+...+32.33
b) S= 1.2+2.3+3.4+...+49.50
Ta có : S = 1.2 + 2.3 + 3.4 + ..... + 32.33
=> 3S = 1.2.3 - 1.2.3 + 2.3.4 - 2.3.4 + ...... + 32.33.34
=> 3S = 32.33.34
=> S = \(\frac{32.33.34}{3}=11968\)
Giá trị của tổng S= 1.2+2.3+3.4+...49.50=?
Tính: S= 1.2+2.3+3.4+....+49.50
Nhân cả 2 vế của S với 3 ta được :
3S = 3(1.2 + 2.3 + 3.4 + ..... + 49.50)
= 1.2.3 + 2.3.3 + 3.4.3 + ... + 49.50.3
= 1.2.3 + 2.3.(4 - 1) + 3.4.(5 - 2) + .... + 49.50.(51 - 48)
= 1.2.3 + 2.3.4 - 1.2.3 + 3.4.5 - 2.3.4 + .... + 49.50.51 - 48.59.50
= (1.2.3 - 1.2.3) + (2.3.4 - 2.3.4) + ......... + (48.49.50 - 48.49.50) + 49.50.51
= 49.50.51
=> S = 49.50.51/3 = 41650
Ta có: 3S=1.2.3+2.3.(4-1)+3.4.(5-2)+...+49.50(51-48)
=1.2.3+2.3.4-1.2.3+3.4.5-2.3.4+....+49.50.51-48.49.50
=49.50.51
=124950
Tính nhanh A = 1/1.2 + 1/2.3 + 1/3.4 + 1/3.4 + ... + 1/49.50
Ta thấy:\(\frac{1}{1.2}=1-\frac{1}{2},\frac{1}{2.3}=\frac{1}{2}-\frac{1}{3},...,\frac{1}{49.50}=\frac{1}{49}-\frac{1}{50}\)
=>\(A=\frac{1}{1.2}+\frac{1}{2.3}+\frac{1}{3.4}+...+\frac{1}{49.50}\)
=>\(A=1-\frac{1}{2}+\frac{1}{2}-\frac{1}{3}+\frac{1}{3}-\frac{1}{4}+...+\frac{1}{49}-\frac{1}{50}\)
=>\(A=1-\frac{1}{50}\)
=>\(A=\frac{49}{50}\)
\(A=\frac{1}{1.2}+\frac{1}{2.3}+\frac{1}{3.4}+...+\frac{1}{49.50}\)
\(\Rightarrow A=1-\frac{1}{2}+\frac{1}{2}-\frac{1}{3}+\frac{1}{3}-\frac{1}{4}+...+\frac{1}{49}-\frac{1}{50}\)
\(\Rightarrow A=1-\frac{1}{50}\)
\(\Rightarrow A=\frac{49}{50}\)
\(A=\frac{1}{1\cdot2}+\frac{1}{2\cdot3}+\frac{1}{3\cdot4}+...+\frac{1}{49\cdot50}\)
\(A=\frac{1}{1}-\frac{1}{2}+\frac{1}{2}-\frac{1}{3}+\frac{1}{3}-\frac{1}{4}+...+\frac{1}{49}-\frac{1}{50}\)
\(A=\frac{1}{1}-\frac{1}{50}\)
\(A=\frac{50}{50}-\frac{1}{50}\)
\(A=\frac{49}{50}\)
Cho A=1/1.2 + 1/2.3 + + 1/ 3.4+...+1/49.50 ; B = 1.2+2.3+3.4+4.5+5.6+...+49.50
Tính 50 mủ 2 A – B/17